2021
DOI: 10.1109/tii.2021.3052182
|View full text |Cite
|
Sign up to set email alerts
|

Stealthy Sensor Attack Detection and Real-Time Performance Recovery for Resilient CPS

Abstract: Cyber-physical attacks exploit intrinsic natures of physical systems and can severely damage cyber-physical systems (CPSs) without being detected by the conventional anomaly detector. In this paper, based on software-defined networking, we propose a holistic resilient CPS framework that can detect, isolate, and recover from cyber-physical attacks in real-time. To show the effectiveness of the proposed framework, we focus on the pole-dynamics attack (PDA), a newly reported stealthy sensor attack that can make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…We implement a wireless NCS testbed. The testbed consists of a physical system emulator [25], two computing systems, two APs, and an attacker, as shown in Fig. 4.…”
Section: A Testbed Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We implement a wireless NCS testbed. The testbed consists of a physical system emulator [25], two computing systems, two APs, and an attacker, as shown in Fig. 4.…”
Section: A Testbed Environmentmentioning
confidence: 99%
“…We use an integrated absolute error (IAE) as a metric to evaluate the recovery performance [25], [27]. IAE is defined as an integral of the absolute value of an error between the DC motor angle θ(t) and reference angle θ r (t).…”
Section: ) When the Attack-induced Delay Is In The Feasible Stability...mentioning
confidence: 99%
“…Pole-dynamics attacks are typical covert cyber-physical attacks based on system theory that tampers with controlrelated information in communication networks. To counter PDA, Kim et al [129] suggested a real-time resilient CPS framework. The proposed architecture is a holistic approach needed to detect, isolate, and recover from the PDA in realtime.…”
Section: Stochastic Resiliencymentioning
confidence: 99%
“…Therefore, stealthiness is a necessary condition, and attack performance is the attacker’s goal. Existing work focuses on FDI attacks with particular stealth performance metrics, such as stealthy attacks [ 15 , 16 , 17 ], covert attacks [ 18 , 19 ], zero-dynamics attacks [ 20 ], optimal stealthy attacks [ 21 ], perfect stealthy attacks [ 22 ], and unpredictable attacks [ 23 ]. These attack strategies have a common design idea, that is, maximizing the attack impacts of the physical plant while ensuring the attacks cannot be detected by some specific detectors.…”
Section: Introductionmentioning
confidence: 99%